Determination of reliable concentrations of pollutants in raw wastewater based on different sampling methods = Wyznaczanie miarodajnych stężeń zanieczyszczeń w ściekach surowych w oparciu o różne metody poboru próbek - Myszograj, Sylwia; Sadecka, Zofia; Qteishat, Omar; Suchowska-Kisielewicz, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this study was to check the extent to which the sampling method and the volume of sewage (size of the wastewater treatment plant) influence the determined daily average concentrations of pollution components. Within three days of dry weather, the composition of two raw sewage wastewater treatment plants was continuously monitored.
Keywords: metody poboru próbek; ścieki; analiza ścieków; oczyszczalnia ścieków; sampling methods; raw sewage; wastewater treatment plant